2018
DOI: 10.1177/0954408918770057
|View full text |Cite
|
Sign up to set email alerts
|

Computational cavitating viscous liquid flows in a pump as turbine and Reynolds number effects

Abstract: Cavitating flows of viscous oils in an experimental centrifugal pump with low specific speed are modeled and simulated by using the time-averaged Navier–Stokes equations and standard [Formula: see text] turbulence model as well as full cavitation model based on the computational fluid dynamics method, when the pump operates in the reverse direction as turbine to generate power. The cavitation characteristics are identified at part-load, best efficiency and over-load points and five viscosities. Effects of visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The cavitation wa more prone to appear in the pump impeller under high viscosity conditions. Li and Zhan [24] also found that an increased viscosity was favorable to cavitation in a pump as th turbine. The cavitation number, σa, is one of the important parameters characterizing the cav itation of the pump.…”
Section: Cavitation Characteristic Curve Of Hampmentioning
confidence: 95%
See 2 more Smart Citations
“…The cavitation wa more prone to appear in the pump impeller under high viscosity conditions. Li and Zhan [24] also found that an increased viscosity was favorable to cavitation in a pump as th turbine. The cavitation number, σa, is one of the important parameters characterizing the cav itation of the pump.…”
Section: Cavitation Characteristic Curve Of Hampmentioning
confidence: 95%
“…The cavitation was more prone to appear in the pump impeller under high viscosity conditions. Li and Zhang [24] also found that an increased viscosity was favorable to cavitation in a pump as the turbine. Under the NPSHAC condition, the NPSHA under different fluid viscosities is show in Figure 7.…”
Section: Cavitation Characteristic Curve Of Hampmentioning
confidence: 96%
See 1 more Smart Citation
“…CFD technology has been found to be effective for analyzing the cavitation zone and associated decreases in inefficiency. The validation of models with the prevailing outcomes allows researchers to redesign, select, and forecast performance [221]. Among the models applied by CFD, Rayleigh-Plesset is the leading model for modeling and prediction of many characteristics of cavitation including the formation, decay, and vapor production rate [222].…”
Section: State-of-the-art Assessment and Evaluationmentioning
confidence: 99%
“…Cavitation is an important source of instabilities, so it was included in the same query as instabilities. In this group, the following topics are addressed: geometry, efficiency, cavitation [4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], flow structures [8,[22][23][24][25], pressure fluctuations [16,21,26,27], vortex rope [27], energy losses when switching from pump to turbine mode [28], and application of entropy production theory for energy losses [29]. None of them addresses the measurement of instabilities.…”
Section: Introductionmentioning
confidence: 99%